Dampak Dana Desa dalam Pembangunan Desa: (Studi di Desa Tunjungtirto Kecamatan Singosari Malang) - Fatah, Zainal; Sholichah, Nihayatus; Pramudiana, Ika Devy (Asketik: Jurnal Agama dan Perubahan Sosial, 2018)
This research is conducted to give an illustration of the extent of the impact of village funds on village development in Tunjungtirto Village Singosari Subdistrict and whether the village funds are used according to the program. The impact analysis focuses on the areas of development which include the construction of basic facilities and infrastructure, the construction of basic social service facilities and infrastructure, and the construction of economic facilities and infrastructure. The conclusions of the research results are: 1. Village Fund Implementation in Tunjungtirto Village has been implemented for a development activity program by development priority set by Permendes PDTT, 2. Determination of the Program of development activity funded by Village Funds is done through the participative process (bottom-up), transparent and accountable by implementing the Deliberation of Village Development Plan (Musrenbangdes). 3. The Impact of Village Funds in the development of village development areas covering basic infrastructure, basic social service facilities, and economic infrastructure has a positive impact for the village community. 4. The impact of village funds on community empowerment is useful in mobilizing household-based economic activities in management, production, and distribution. 5. The impact of Village Funds for Village Governments can give an acceleration of village development to achieve the vision and mission of Tunjungtirto village government in RPJMDes.